2018
DOI: 10.1002/jbio.201800075
|View full text |Cite
|
Sign up to set email alerts
|

Argon plasma coagulation of actinic keratoses imaged by optical coherence tomography: An in vivo study indicating a possible lesion‐directed treatment

Abstract: Actinic keratoses (AKs) can progress into invasive squamous cell carcinoma and thus may become a life threatening disease. Argon plasma coagulation (APC) might complement the therapeutic armamentarium in particular for AK lesions. However, there is no data on APC-induced micromorphological changes following the treatment of AKs. We aimed to determine in vivo APC-induced effects on the epidermis and dermoepidermal junction (DEJ) zone in AK lesions. We performed APC in 108 AKs using the spray mode with a power s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
4
2
2
Order By: Relevance
“…In this study we also aimed to investigate the effect of CAP on the HFUS parameters of both lesional and chronically photodamaged skin surrounding the lesions. To date, the biological effects of CAP on AKs have not been evaluated through non-invasive imaging techniques, with the exception of a study involving optical coherence tomography (OCT), which showed a clearly demarcated dermoepidermal junction and no residual epidermal tissue left in 74% lesions after CAP [ 32 ]. Notwithstanding, given the different resolution and penetration capabilities of OCT and HFUS, the results of our study are unlikely to be comparable to those obtained with OCT.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we also aimed to investigate the effect of CAP on the HFUS parameters of both lesional and chronically photodamaged skin surrounding the lesions. To date, the biological effects of CAP on AKs have not been evaluated through non-invasive imaging techniques, with the exception of a study involving optical coherence tomography (OCT), which showed a clearly demarcated dermoepidermal junction and no residual epidermal tissue left in 74% lesions after CAP [ 32 ]. Notwithstanding, given the different resolution and penetration capabilities of OCT and HFUS, the results of our study are unlikely to be comparable to those obtained with OCT.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that an annual risk of an individual AK sun damage becoming a malignancy amounts to 0.025-16%. It is significantly higher in cases of numerous foci, especially when they cover the skin surface extensively [6].…”
Section: Wprowadzeniementioning
confidence: 98%
“…Szacuje się, że roczne ryzyko przemiany złośliwej pojedynczego ogniska AK wynosi 0,025-16%. Jest ono znacznie wyższe w przypadku występowania licznych zmian, zwłaszcza zajmujących rozległe powierzchnie skóry [6].…”
Section: Objectiveunclassified
See 2 more Smart Citations